The Correlational Study Between Seventh Grade Students’ Self-Confidence and Their Speaking Skill in Self-Introduction at MTs Darul Ulum Assurur Across Their Cognitive Learning Styles - Fatayati, Roisatul (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2024)
Self-confidence is an important part of speaking skills, as it can provide enthusiasm. If learners are high in confidence, they will achieve the best performance in speaking skills. Studies regarding the factors that influence students' self-confidence are still very limited. Some previous studies mostly discussed the correlation between self-confidence and speaking. Besides self-confidence, there are other factors that can affect students’ self-confidence, namely cognitive learning style. This research used quantitative research method and by applying correlational design. This research was found that, the product moment score were rcount1 = 0.631 (field Independent), rcount2 = 0.558 (field Dependent) and rtable score were rtable1 = 0.455, rtable2 = 0.349. So, the rcount1 and rcount2 is more than rtable1 and rtable2 (0.631> 0.455 and 0.558 > 0.349). Which indicated that there is a significant correlation between the seventh grade students’ self-confidence and their speaking skill in self introduction at MTs Darul Ulum Assurur across their cognitive learning style. It can be concluded that the field independent coefficient correlation is higher than the field dependent (rcount1 > rcount2 = 0.631 > 0.558) It means that if students' self-confidence is high then the students can speak fluently and it implicate that the teacher should design a teaching and learning process where the students learn independently. Key Words: Self-Confidence, Speaking, Field Independent, Field Dependent